Osteoclast: like giant cell undiferrentiated pancreatic tumor diagnosed by means of EUS guided FNA - Kalogeraki, Alexandra; Mouzas, Ioannis; Koutroubakis, Ioannis E; Moustou, Eleni; Lappa, Eleni; Tamiolakis, Dimitrios; Machaira, Aggeliki; Orfanoudaki, Eleni; Kalaitzakis, Evangelos (Acta Biomedica Atenei Parmensis, 2021)
Objective: Osteoclast-like giant cell tumours are rare abdominal malignant neoplasms mainly arising in the pancreas. Because of their rarity, clinical and cytopathology reports are very limited, and sonographic features have not been clearly specified ; these tumors are easily misdiagnosed by ultrasound as mucinous cystic tumors (MCTs) or solid pseudopapillary neoplasms (SPNs). Case study: We report a case of osteoclast like giant cell tumor arising in the pancreas of an 80 year old female patient offered by EUS-FNA cytology on direct and cell block slides. A biphasic pattern composed by a malignant mononuclear cell component and a giant cell component were hallmarks to the diagnosis. Conclusion: Our case highlights the performance of EUS-FNA in the diagnostic approach of abdominal tumours and the significance of cell block method in the interpretation of osteoclast-like giant cell pancreatic tumour.